Strategic Firms and Endogenous Consumer Emulation* - Kircher, Philipp; Postlewaite, Andrew (Quarterly Journal of Economics, 2008)
Better-informed consumers may be treated preferentially by firms because their consumption serves as a quality signal for other customers. For normal goods this results in wealthy individuals being treated better than poor individuals. We investigate this phenomenon in an equilibrium model of social learning with heterogeneous consumers and firms that act strategically. Consumers search for highquality firms and condition their choices on observed actions of other consumers. When they observe consumers who are more likely to have identified a high-quality firm, uninformed individuals will optimally emulate those consumers. One group of consumers arise endogenously as “leaders” whose consumption behavior is emulated. Follow-on sales induce firms to give preferential treatment to these lead consumers, which reinforces their learning. “One very clear impression I had of all the Beautiful People was their prudence. It may be that they paid for their own airline tickets but they paid for little else.” James Brady, Press Secretary to Ronald Reagan From Superchic, Little, Brown 1974